Analysis of Risk Behavior and Hypertension Prevention in Productive Age Communities in the Work Area of the Tapos Health Center UPTD 2025 - Darmaja, Sobar; Nina; Darmadi, Nadya; Aulia, Septiana Putri; Sativa, Siti Oriza; Hartanti, Tety; Zyawala, Xyaqwa Dexta; Andryanto, Yosef Dimas (LPPM Universitas Mohammad Husni Thamrin, 2025)
Non-communicable diseases (NCDs) such as hypertension are now a major challenge in health development in Indonesia. Hypertension, or high blood pressure, is a chronic condition that occurs when blood pressure in the arteries is persistently elevated and is a major risk factor for heart disease, stroke, and kidney failure. Hypertension is a non-communicable disease that is a major health challenge, especially in the productive age group. The causes of hypertension in the productive age group are diverse, ranging from consumption of foods high in salt and fat, lack of physical activity, smoking habits, and psychological stress due to work pressure. Lack of awareness of early detection and low knowledge about a healthy lifestyle also exacerbate the situation. Lack of knowledge about how to prevent hypertension can influence attitudes towards hypertension prevention. This study aims to analyze risk behaviors and hypertension prevention efforts in the Tapos Community Health Center (Puskesmas) work area. Hypertension is a disease with the highest number of visits, so identifying risk behaviors and appropriate prevention strategies is necessary. This study used a descriptive analytical approach with qualitative methods through observation, interviews, and literature review. Data were obtained from a survey of the productive age population and the 2024 health profile of the Tapos Community Health Center (Puskesmas). Results indicate that poor stress management, unhealthy lifestyles, and low public awareness are the main triggers of hypertension. Control efforts focus on education, promoting a healthy lifestyle, and utilizing traditional herbal remedies (TOGA) as a non-pharmacological therapy.